Updated catalogue of Iranian Anthocoridae (Hemiptera: Heteroptera: Cimicomorpha) - Ostovan, Hadi; Ghahari, Hassan; Moulet, Pierre (Zootaxa, 2017)
The published data on Iranian Anthocoridae (Hemiptera) are summarized in this paper. In total 51 species of three subfamilies Anthocorinae, Lyctocorinae and Scolopinae within 10 genera (Amphiareus Distant, Anthocoris Fallén, Buchananiella Reuter, Cardiastethus Fieber, Dufouriellus Kirkaldy, Elatophilus Reuter, Lyctocoris Hahn, Orius Wolff, Temnostethus Fieber, and Xylocoris Dufour) are listed as the fauna of Iran. Xylocoris (Xylocoris) ciliatus (Jakovlev, 1877) is new record for the fauna of Iran.